Long-term results of operations for hernias of the esophageal orifice of the diaphragm depending on the performance of vagotomy - A. N. Vachev; S. V. Dergal'; V. K. Koryttsev; E. E. Adyshirin-Zade (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Introduction. Hernia of the esophageal orifice of the diaphragm, complicated by reflux esophagitis, is one of the most common gastroenterological diseases, occupying the first place among all benign pathology of the cardiofundal zone. Typical complications of this pathology are esophagitis of varying severity, bleeding from the esophagus, peptic stricture and shortening of the esophagus, Barette's esophagus, ulcer and cancer of the esophagus. Indications for surgery include severe reflux esophagitis, the development of complications, and the failure of conservative therapy.Objective: to evaluate the effect of stem vagotomy on the long-term results of surgical treatment of patients with hiatal hernia complicated by reflux esophagitis.Object and methods. The long-term treatment outcomes of 130 patients were studied. All patients had increased acid production. The patients were divided into two groups: group I – 77 patients who underwent correction of hiatal hernia in isolation; group II – 53 patients who had correction of hiatal hernia supplemented by stem vagotomy. In group I, anatomical recurrence of hiatal hernia was diagnosed in 14 patients (18.2%), and in group II – in 1 (1.9%) patient. In the long-term postoperative period, none of the patients who underwent stem vagotomy were diagnosed with severe reflux esophagitis. While in patients who did not undergo stem vagotomy, a severe form of reflux esophagitis was found in 10.3% of patients.Conclusion. In patients with hiatal hernia with increased acid production complicated by reflux esophagitis, it is advisable to supplement the correction operation with a stem vagotomy. This tactic leads to a statistically significant decrease in the number of relapses in the long-term period.